New Therapies and Immunological Findings in Cutaneous T-Cell Lymphoma - Fujii, Kazuyasu (Frontiers in Oncology, 2018)
Primary cutaneous lymphomas comprise a group of lymphatic malignancies that occur primarily in the skin. They represent the second most common form of extranodal non-Hodgkin’s lymphoma and are characterized by heterogeneous clinical, histological, immunological, and molecular features. The most common type is mycosis fungoides, and its leukemic variant, Sézary syndrome. Both diseases are considered Th2 diseases. Not only the tumor cells, but also the tumor microenvironment can promote Th2 differentiation, which is beneficial for the tumor cells because a Th1 environment enhances antitumor immune responses. This Th2-dominant milieu also underlies the infectious susceptibility of the patients. Many components, such as tumor-associated macrophages, cancer-associated fibroblasts, and dendritic cells, as well as humoral factors, such as chemokines and cytokines, establish the tumor microenvironment, and can modify tumor cell migration and proliferation. Multi-agent chemotherapy often induces immunosuppression, resulting in an increased risk of serious infection and poor tolerance. Therefore, overtreatment should be avoided for these types of lymphoma. Interferons have been shown to increase the time to next treatment to a greater degree than has chemotherapy. The pathogenesis and prognosis of cutaneous T-cell lymphoma differs markedly among the subtypes. In some aggressive subtypes of cutaneous T-cell lymphomas, such as primary cutaneous gamma/delta T-cell lymphoma and primary cutaneous CD8+ aggressive epidermotropic cytotoxic T-cell lymphoma, hematopoietic stem cell transplantation should be considered, whereas overtreatment should be avoided with other, favorable subtypes. Therefore, a solid understanding of the pathogenesis and immunological background of cutaneous lymphoma is required to better treat patients who are inflicted with this disease. This review summarizes the current knowledge in the field to attempt to achieve this objective.